Automatic control of the boiler heat power based on changing hydrocarbonfuelʼs calorific value - Beglov, K.; Kozlov, O.; Kondratenko, Yu.; Markolenko, T.; Krivda, V. (Проблеми керування та інформатики, 2023)
This article is dedicated to the development and research of an approach for automatic control of boiler thermal power by compensating load disturbances through the regulation of the composition of the burned hydrocarbon fuel mixture. The proposed approach allows for the design of an automatic control system (ACS) for the boiler, enabling the creation of conditions for forming and determining the current heat-generating capacity of the gas mixture that corresponds to the current thermal load of the boiler, as well as determining the flow and temperature of the flue gases in the boiler. Дана стаття присвячена розробці та дослідженню підходу до автоматичного керування тепловою потужністю котла при компенсації збурень навантаження шляхом регулювання складу спалюваної вуглеводневої паливної суміші. Запропонований підхід дає можливість здійснювати проєктування системи автоматичного керування (САК) котлом з можливістю створення умов для формування та визначення поточної теплотворної здатності суміші газів, яка відповідає поточному тепловому навантаженню котла, а також визначення витрати і температури димових газів у котлі.